Interventions designed to promote the consumption of locally produced foods: a scoping review - Haynes, Emily; Brown, Catherine R.; Halliday, Cassandra; Alcantara, Lutgardo; Cayetano, Cristobal; Creencia, Lota; Gajardo, Lea Janine; Goodwin, Amanda; Guell, Cornelia; Howitt, Christina; Iese, Viliamu; Karley, Alison; et al. (Frontiers in Sustainable Food Systems, 2025)
IntroductionFood system transformation is required for planetary health. Localizing food systems and applying agroecological principles to food production and supply have been suggested to support a resilient and sustainable food system. This scoping review aimed to map the implementation of interventions designed to promote the consumption of locally produced food, their application of agroecological principles and the outcomes evaluated, across Global North and Global South countries.MethodsSearches were conducted systematically in 15 databases. Screening was conducted against criteria to identify eligible studies and data extracted in REDCap and EPPI Reviewer. Data were narratively synthesized, and results displayed as tables, figures and an interactive evidence gap map.ResultsWe found 147 eligible studies describing interventions to promote the consumption of locally produced food. Only two studies reported the impact of intervention on local versus non-local food procurement and we identified a lack of a standard framework for assessing the impact of changing food source practice. Most studies reported dietary outcomes, mainly fruit and vegetable intake, and less used metrics for dietary diversity, particularly in the Global North. A small proportion (5%) reported ecosystem related outcomes. All home growing interventions were conducted in the Global South and most school-based growing interventions were conducted in the Global North. Agroecological principles were applied to Global North and Global South interventions, but a greater proportion of the Global South studies applied agroecological practices (GS 30%; GN 4%).DiscussionThis map of experimental research on local food interventions identifies key differences in intervention types and agroecological principles and practices applied in Global South and Global North countries, potential learnings between settings, and gaps in the evidence. We call for greater coherence in the development, evaluation and reporting of local food interventions to enable synthesis on their effectiveness and to strengthen evidence on local food approaches aiming to improve human nutrition and planetary health.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023428104, identifier [CRD42023428104].